Factors affecting the in-situ hydrolysis of empty fruit bunches in ionic liquid compatible cellulase system - Elgharbawy, Amal A.M.; Alam, Md. Zahangir; Moniruzzaman, Muhammad; Kabbashi, Nassereldeen Ahmed; Jamal, Parveen (Penerbit Akademia Baru, 2018)
Utilization of the abundant raw materials in Malaysia as well as surmounting the obstacle of the shortcoming of fossil fuels resources are current concerns of the research. Cellulase development aims to enhance the bioethanol production from lignocellulosic biomass such as empty fruit bunches (EFB) that resists enzymatic hydrolysis due to its complex structure. Hence, ionic liquids (ILs) have been introduced with the ability to disrupt the lignocellulose to be accessible by enzymes and thus it is expected to achieve a significant improvement by conducting both treatment and hydrolysis in one step by leaping cellulose regeneration. Palm kernel cake (PKC) was utilized as the primary media for cellulase production through solidstate bioconversion (SSB) by Trichoderma reesei. Factors that affect the hydrolysis in the ionic liquid-cellulase (IL-E) system was investigated using one-factor at a time (OFAT) and reducing sugar obtained as the response to the study. It was found that the biomass could be loaded up to 35% (w/v) and agitation has influenced the rate of reducing sugar production where increasing the speed was associated with higher concentration. Higher IL concentration in the combined system caused lower enzymatic activity and hence, less sugar was produced. The results obtained can be employed for the one-step process in the conversion of EFB into fermentable sugar.